Development of Housing Standards and Spatial Design Guidelines for Mobility Handicaps in Thailand - Sasicha Sukkay; Prapatpong Upala (My University, 2017)
The objectives of this research are 1) to compare the standards of housing design for mobility disabled at the domestic and universal levels, 2) to standardize the developing process of housing design guideline for mobility handicapped properly with the context of Thailand, and 3) to evaluate the proficiency of the guideline by employing both qualitative and quantitative research methods. Regarding the guidelines comparison, the results indicated that the available housing design guidelines in Thailand had excluded the spatial allocation standard for supporting the mobility dependency as well as some particular dwelling functions had been abandoned from these guidelines. Furthermore, it appeared that these design guidelines were not constituted based on the participatory of multidisciplinary experts, for instance, medical and architectural professionals. This research had initiated an evaluating process for the guideline’s competence by using four indicators,namely, 1) comprehension, 2) completeness, 3) convenience, and 4) composition of design. The rating scale questionnaires were distributed to the two sampling groups comprising the group of 30 experienced Government agencies and the group of 30 mobility handicapped. The data collection consisted of two main steps: 1) the assessment of the comparative study-based guideline and 2) the assessment of the participatory-based guideline. The data retrieved from these two phases were analyzed by the inferential statistics, Paired Sample t-test. The results revealed the differences between these two sampling groups in every design category at the significance level of 0.05. It was clear that the participatory-based guideline was more efficient than the comparative study-based guideline (p ≤ 0.005). Besides, the evaluating scores addressed by the group of experienced Government agencies and the group of mobility disabled representative were discovered significantly contrary.
Keywords: Guideline; Research Design; Sample (material); Underground infrastructure and sustainability